Implementasi Metode Takrir dalam Meningkatkan Hafalan Al-Qur'an: Implementation of the Takrir Method in Enhancing Quran Memorization - Ridiawati, Ridiawati; Komarudin, Komarudin; Rochman, Asep Saepul; Hariyanto, Teguh; Jaelani, Deny Ahmad (Sekolah Tinggi Agama Islam Kharisma Cicurug Sukabumi, 2025)
This study examines the effectiveness of the takrir method in enhancing Qur'an memorization at SMP IT Rohmatul Ummah. The takrir method, meaning